Altered Regional Homogeneity in Patients With Congenital Blindness: A Resting-State Functional Magnetic Resonance Imaging Study - Hu, Jiong-Jiong; Jiang, Nan; Chen, Jun; Ying, Ping; Kang, Ming; Xu, San-Hua; Zou, Jie; Wei, Hong; Ling, Qian; Shao, Yi (Frontiers in Psychiatry, 2022)
Backgroud: In patients with congenital blindness (CB), the lack of any visual experience may affect brain development resulting in functional, structural, or even psychological changes. Few studies to date have addressed or focused on the synchronicity of regional brain activity in patients with CB. Our study aimed to investigate regional brain activity in patients with CB in a resting state and try to explain the possible causes and effects of any anomalies. Methods: Twenty-three CB patients and 23 healthy control (HC) volunteers agreed to undergo resting state functional magnetic resonance imaging (fMRI) scans. After the fMRI data were preprocessed, regional homogeneity (ReHo) analysis was conducted to assess the differences in brain activity synchronicity between the two groups. Receiver operating characteristic (ROC) curve analysis was used to explore whether the brain areas with statistically significant ReHo differences have diagnostic and identification values for CB. All CB patients were also required to complete the Hospital Anxiety and Depression Scale (HADS) to evaluate their anxiety and depression levels. Results:The results showed that in CB patients mean ReHo values were significantly lower than in HCs in the right orbital part of the middle frontal gyrus (MFGorb), bilateral middle occipital gyrus (MOG), and the right dorsolateral superior frontal gyrus (SFGdl), but significantly higher in the left paracentral lobule (PCL), right insula and bilateral thalamus. The ReHo value of MFGorb showed a negative linear correlation with both the anxiety score and the depression score of the HADS. ROC curve analysis revealed that the mean ReHo values which differed significantly between the groups have excellent diagnostic accuracy for CB (especially in the left PCL and right SFGdl regions). Conclusions: Patients with CB show abnormalities of ReHo values in several specific brain regions, suggesting potential regional structural changes, functional reorganization, or even psychological effects in these patients. FMRI ReHo analysis may find use as an objective method to confirm CB for medical or legal purposes.